Why Planning Does Not Work. Land Use Planning and Residents Rights in Tanzania - Nnkya, Tumsifu Jonas (Book collections on Project MUSE., 2007)
Lack of transparency and accountability in the planning practice allow for misuse and abuse of the planning system to serve the interests of the more powerful and influential groups, including those entrusted with the powers of planning. The outcomes of a non-inclusive, non-transparent and insensitive planning include: insecurity of land tenure rights and subsequently investments in land; poverty; informal land subdivision and building; unplanned spatial growth and endless conflicts in land development. These are detrimental to the residents and erode their trust and confidence in the governme.